Внутрішня торгівля в Україні: стан та перспективи розвитку - Демчук, Наталья Іванівна; Demchuk, Natalia; Безугла, Людмила Сергіївна; Bezugla, Ludmila; Ткаліч, Ольга Вікторівна; Tkalich, Olga (Чорноморський національний університет імені Петра Могили, ТОВ `ДКС Центр`, 2019)
У статті досліджено стан розвитку внутрішньої торгівлі в Україні. Аналізуються тенденції та проблеми розвитку роздрібної та оптової торгівлі. На основі цього визначено, що в структурі обсягу виробленої продукції частка оптової та роздрібної торгівлі протягом досліджуваного періоду зросла однак, спостерігалося і її зменшення. Здійснено аналіз виробництва та розподілу валового внутрішнього продукту за видами економічної діяльності. На цій основі визначено вузькі місця у їх розвитку та окреслено основні проблеми. Наголошено, що з позицій системного підходу внутрішню торгівлю можна і потрібно розглядати як соціальноекономічну систему, в основі діяльності якої лежать потреби людей, задоволення яких за! безпечується шляхом пропозиції і реалізації широкого та глибокого асортименту товарів народного споживання, який формується завдяки узгодженій взаємодії підгалузей оптової і роздрібної торгівлі. Разом з тим, у галузі торгівлі, яка в Україні демонструє динамічне зростання як обсягів реалізації товарів, так і фінансових показників торговельно!господарської діяльності. The article analyzes the state of development of domestic trade in Ukraine. The tendencies and problems of development of retail and wholesale trade are analyzed. On the basis of this, it is determined that the share of wholesale and retail trade in the structure of the volume of manufactured goods increased during the investigated period, however, and its decrease was observed. The analysis of production and distribution of gross domestic product by types of economic activity was carried out. On this basis, bottlenecks are identified in their development and the main problems are outlined. It is emphasized that from the point of view of a systematic approach, domestic trade can and should be considered as a socio economic system, the basis of which is the needs of people, whose satisfaction is ensured by proposing and implementing a wide and deep assortment of consumer goods, which is formed due to the coordinated interaction of subsectors of wholesale and retail trade. At the same time, in the trade sector, which in Ukraine shows a dynamic growth both in sales volumes and financial indicators of trade and economic activity. He lack of a strategic approach to solving the saturation of the domestic market due to an appropriate increase in domestic production through the development of import substitute products leads to the formation of a high dependence of the domestic market on imports, as well as the need to increase exports to cover the current account deficit of the balance of payments. The openness of the national economy strengthens the vulnerability of the domestic market to fluctuations in the external environment and unfavorable world trends. Consequently, there is a need to reduce the import dependence of commodity markets, to create conditions for reducing dependence on the situation of external markets, to ensure the positive impact of imports on production, strengthening on this basis the competitiveness of the domestic economy. Significant imbalances in the development of the domestic market as a result of the exacerbation of the situation in eastern Ukraine, a significant devaluation of the hryvnia against the US dollar. This is manifested primarily in: the crazy fall in the indices of production of the basic industries of the economy in 2015; decrease in wholesale and retail turnover due to lower purchasing power of the population; a significant increase in prices for foodstuffs, transport, housing and communal services, agricultural products, non food products, medicines; complex financial and economic conditions of the economy, the crisis in the financial and credit sector has led to a significant congestion of business entities in the middle of the country.
Domestic trade in Ukraine: status and development prospects
Keywords: внутрішня торгівля; domestic trade; роздрібна торгівля; retail trade; оптова торгівля; wholesale trade; оптовий товарооборот; wholesale trade turnover; роздрібний товарооборот; retail trade turnover